PENANGANAN PERIOPERATIF ANESTESI PADA RESEKSI FEOKROMOSITOMA - Laihad, Mordekhai Leopold (JURNAL BIOMEDIK : JBM, 2011)
Abstract: Definitive therapy of pheochromocytoma is a surgical resection. Anesthetic perioperative management toward pheochromocytoma resection plays a very important role in decreasing morbidity and mortality. This management includes preoperative preparations, intraoperative management and postoperative management. The preoperative preparations involving multidiscipline approaches have several objectives: controlling blood pressure, creating an adequate intravascular volume, assessing effects of the disease to end-organs, recognizing conditions pertaining to pheochromocytoma, and controlling blood glucose and electrolyte levels. The intraoperative management is a continuation of the preoperative preparations. Its main objective is to preclude the event of hypertension crisis. The postoperative management is aimed to anticipate important complications which possibly occur in the early postoperative period, such as: hypertension, hypotension, and hypoglycemia. Keywords: pheochromocytoma, anesthesia, management, preoperative, intraoperative, postoperative.   Abstrak: Terapi definitif terhadap feokromositoma adalah reseksi. Penanganan perioperatif anestesi pada reseksi feokromositoma sangat berperan dalam menekan morbiditas dan mortalitas. Penanganan ini meliputi persiapan preoperatif, penangananan intraoperatif dan penanganan pasca bedah. Persiapan preoperatif dilakukan secara multidisiplin dan bertujuan untuk mengendalikan tekanan darah, mencukupi volum intravaskuler, menilai pengaruh penyakit terhadap end-organ, mengenali dampak dari kondisi-kondisi yang terkait dengan feokromositoma, serta normalisasi kadar glukosa dan elektrolit. Penanganan intraoperatif merupakan kesinambungan dari persiapan preoperatif dan bertujuan utama menghindari terjadinya krisis hipertensi. Penanganan pasca bedah bertujuan untuk mengantisipasi kemungkinan terjadinya komplikasi penting pada periode pasca bedah dini yakni hipertensi, hipotensi dan hipoglikemi. Kata kunci: feokromositoma, anestesi, penanganan, preoperatif, intraoperatif, pasca bedah.